The (potential) demise of HRM? - Dundon, Tony; Rafferty, Anthony (Human resource management journal, 2018)
This article seeks to provoke that human resource management (HRM), both as an academic field of study and as a form of professional practice, is at risk of impoverishment. The main reasoning for this is because of ideological individualism and marketisation with an attendant neglect on wider organisational, employee, and societal concerns. Following a review of the context of financialised capitalism, three contemporary developments in HRM are used to illustrate the argument: reward strategies, talent management, and high performance work systems. Implications for the practice of HRM and the way the subject area is taught in mainstream business schools are considered. Video